Development of French Contemporary Dance An Interaction between Public Intervention and Market Mechanisms - Germain-Thomas, Patrick 1961- (Edinburgh: Edinburgh University Press, 2017)
RESUMEN: In France, an academic view of dance held sway until the 1960s. However the growing recognition of contemporary dance by the French ministry of culture and by local authorities since the 1970s culminated in the constitution of an artistic world distinct from that of classical dance. A mixed economic system has been set up, with contemporary dance companies depending not only on subsidies but also on funding from theatres and festivals, which either purchase or coproduce performances. This "subsidized market" combines the allocations of subsidies by public bodies and the relatively-free decisions of venue managers. In spite of substantial increases in scheduling and attendance figures, this market is characterized by a structural imbalance linked to a gap between the number of performances produced annually and the outlets offered by the distribution networks. The enlarging of the audience is therefore essential to the future of this artistic movement in France. PALABRAS CLAVE: contemporary dance, creation, cultural policy, scheduling, audience development.